A triple co-culture method to investigate the effect of macrophages and fibroblasts on myoblast proliferation and migration - Colin Venter; Carola Niesler (BioTechniques)
The communication between nonmyogenic cells, such as macrophages and fibroblasts, and myoblasts is crucial for successful skeletal muscle repair. In vitro co-culture methods can be used to increase our understanding of these cellular interactions; however, current protocols are restricted to two, often physically separate, cell populations. Here, we demonstrate a novel, inexpensive in vitro triple co-culture method that facilitates the co-culture of at least three cell populations with some degree of cell–cell contact. Using this method, we determined the effect of macrophages and fibroblasts on myoblast proliferation and migration. A significant increase in myoblast proliferation and migration was observed following co-culture with either macrophages or fibroblasts. However, triple co-culture of macrophages, fibroblasts, and myoblasts revealed that the presence of macrophages prevented fibroblasts from maintaining this positive effect on myoblast migration. Macrophages, on the other hand, continued to promote myoblast proliferation whether in the presence of fibroblasts or not. Our triple co-culture system highlights the significance of multicellular communication in regulating myoblast proliferation and migration and emphasizes the importance of more complex co-culture systems when investigating myogenesis in vitro.